2023
DOI: 10.1039/d3ta01503c
|View full text |Cite
|
Sign up to set email alerts
|

3D microstructural characterization of Ni/yttria-stabilized zirconia electrodes during long-term CO2 electrolysis

Abstract: The solid oxide electrolysis cell (SOEC) is one of the most promising energy conversion devices due to its high efficiency and gas flexibility. However, its performance degradation in long-term operation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The variation in f surf was controlled by multiplying A and B by a common factor of f surf / f 0 surf , where f 0 surf is the reference surface energy. 19 A tuning function of W = −9.35 W ad + 4.69 was extrapolated to control the variation in W ad by setting a reference contact angle under OCV conditions to 115°, 14 and another contact angle under high polarization φ = 0.1 V to 18°, as shown in Fig. S0 in the ESI † 21 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The variation in f surf was controlled by multiplying A and B by a common factor of f surf / f 0 surf , where f 0 surf is the reference surface energy. 19 A tuning function of W = −9.35 W ad + 4.69 was extrapolated to control the variation in W ad by setting a reference contact angle under OCV conditions to 115°, 14 and another contact angle under high polarization φ = 0.1 V to 18°, as shown in Fig. S0 in the ESI † 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The observations in our previous work indicated that current plays a major role in driving Ni migration, while the contribution of the gas diffusion pathway is minor. 14 The Ni–YSZ contact angle gradient caused by the current could play an important role in driving the Ni surface diffusion in different gas environments. To verify the influence of the contact angle gradient along the Ni–YSZ interface, the simplified PF simulations were rerun by introducing continuous gradients for both f surf and W ad along the x -axis by using ∇ W = −0.01/voxel and ∇( f surf / f 0 surf ) = 0.01/voxel, while W = 4 and ( f surf / f 0 surf ) = 0.75 were set at the center indicated by the dashed line, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional Ni-YSZ is widely used as electrode materials for SOEC. Nevertheless, the application of Ni-YSZ for the CO 2 electrochemical reduction reaction is hindered by problems such as impurity gas poisoning, redox instability, and coke deposition at high CO concentration. Perovskite oxides with good mixed electron–ion conductivity (MEIC) are ideal alternative cathodes for coelectrolysis using SOEC. For instance, Cho et al combined microkinetic analysis and density-functional theory calculations to obtain a volcano plot of the electrocatalytic activity of coelectrolysis, confirming that Fe, Ru, and Co had superior activity than Ni in the CO 2 /H 2 O coelectrolysis .…”
Section: Introductionmentioning
confidence: 99%